2019
DOI: 10.3390/s20010096
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Highly Sensitive Hydrogen Sensor Based on Pt-WO3/Si Microring Resonator

Abstract: Hydrogen gas has attracted attention as a new energy carrier, and simple but highly sensitive hydrogen sensors are required. We fabricated an optical hydrogen sensor based on a silicon microring resonator (MRR) with tungsten oxide (WO 3 ) using a complementary metal-oxide-semiconductor (CMOS)-compatible process for the MRR and a sol-gel method for the WO 3 layer and investigated its sensing characteristics at device temperatures of 5, 20, and 30 • C. At each temperature, a hydrogen concentration of as low as 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…A control unit is used to switch each SE and state. It can change and activate SE conditions according to flow routing requirements [21]. Fig.…”
Section: A Primary 2×2 Switch and 4×4 Switchesmentioning
confidence: 99%
“…A control unit is used to switch each SE and state. It can change and activate SE conditions according to flow routing requirements [21]. Fig.…”
Section: A Primary 2×2 Switch and 4×4 Switchesmentioning
confidence: 99%
“…The findings showed, I-V characteristics revealed an ohmic behaviour of the contacts to the sensor and the complex impedance spectrum (IS) showed a single semicircle with shrinkage in the diameter when the temperature is increased. Matsuura et al [18] successfully found that Pt-WO 3 /Si microring resonator able to detect hydrogen gas as low at concentration of 0.1 vol% with a response time of 10 s at each temperature of 5, 20, and 30˚C. The experiment also revealed gas sensitivity increased when temperature is decreasing.…”
Section: Introductionmentioning
confidence: 98%
“…Wavelength tunable laser diodes with a broad wavelength tunable range are used as light sources for wavelength division multiplexing, [1][2][3] light detection and ranging (LiDAR), and gas sensing. 4,5) In LiDAR systems, wavelength tunable laser diodes are used for solid-state beam scanners, which can control the direction of a light beam without moving parts by changing the lasing wavelength. [6][7][8][9][10] External-cavity laser diodes with silicon photonics doublering resonators as wavelength filters have a broad wavelength tunable range by the vernier effect.…”
Section: Introductionmentioning
confidence: 99%